Factors Affecting Satisfaction in Online Financial Transactions: a study of Brazilian home brokers - Ferreira, Jorge Brantes; Freitas, Angilberto Sabino de; Nunes, Deborah Coutinho Gil; Giovannini, Cristiane Junqueira (Review of Business Management, 2014)
This paper evaluated consumers’ perceptions of Brazilian Home Broker services in the online environment. Based on the model suggested by Balasubramanian, Konana and Menon (2003), the effects of relevant online consumer behavior constructs on customer satisfaction with the service were analyzed. Constructs such as perceived operational competence, willingness to trust and perceived environmental security were employed, in a model fully mediated by trust. A questionnaire with scales previously used in literature was employed to measure the relevant constructs and structural equations applied to analyze the relationships found. Results show a strong relationship between perceived environment security and perceived operational competence, indicating that trust formation precedes satisfaction in online financial services transactions within the Brazilian context.